Printed asymmetric microcapsules: Facile loading and multiple stimuli-responsiveness; Biomaterials Advances; Vol. 136 - Kudryavtseva V. L. Valeriya Lvovna; Bukatin A. F. Anton Filippovich; Vyacheslavova E. A. Ekaterina Aleksandrovna; Gould J. David; Sukhorukov G. B. Gleb Borisovich (2022, 2022)
Title screen